Global Perspective on the Management of Peyronie's Disease - Moisés da Silva, Gabriel Veber; Dávila, Francisco Javier; Rosito, Tiago Elias; Martins, Francisco E. (Frontiers in Reproductive Health, 2022)
Introduction Peyronie's disease is the disease that results in an alteration in the curvature of the penis, which can lead to a shortening of length, pain in erection, or difficulties in penetration, thus leading the patient to psychological alterations due to loss of functionality such as aesthetic alteration. That is why there are several studies to define the best form of treatment, which currently continues to be the first choice surgical treatment. Objective We present the most recommended therapies for Peyronie's disease and suggest an algorithm as a guide to direct therapy. Methods We used the PubMed platform to review the literature related to Peyronie's disease. Various editorials were reviewed as well as original articles and reviews focusing on the various treatments as well as their indications and results. Results Peyronie's disease in which conservative or drug treatment does not have a response, surgical treatment with corporoplasty, penile prosthesis implantation or both may be indicated. Corporoplasty refers to both the plication of the tunica albuginea as well as the incision of the tunica with the placement of a graft. An accurate history should always be carried out to identify erectile dysfunction as well as to be able to guide you on the repercussions of the treatment. If refractory erectile dysfunction is present, placement of a penile prosthesis with or without further adjunctive straightening maneuvers is recommended. We reviewed the indications, advantages, disadvantages, and results of the available techniques, and proposed a surgical treatment algorithm. Conclusion Penile shortening procedures are usually indicated in curvatures <60°, in penises with adequate length. Partial excision/incision and grafting are indicated for curvatures >60°, hourglass or hinge deformities, and short penises, if the patient's erectile function is adequate. The presence of “borderline” erectile function and/or ventral curvature tilts the choice toward shortening procedures, and refractory erectile dysfunction is an indication for penile prosthesis placement. An accurate risk/benefit assessment of the individual patient as well as meticulous patient counseling are critically important.